PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA MELALUI PROFESIONALISME PEGAWAI PT KERETA API LOGISTIK - jurnalmap map; Agung Sarjono; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This study aims to determine and explain the effect of competence and work motivation on performance through the professionalism of employees of PT Kereta Api Logistik from a subsidiary of PT Kereta Api Indonesia, in Regional 3 East Java, especially the Surabaya area. The method used in this research is a quantitative approach. Data was collected by conducting a survey. The results showed that professionalism had an effect on employee performance at PT. Logistics Railroad. This is because the professionalism of employees has been in accordance with the performance of employees at PT. Logistics Railroad. Competence has a direct influence on professionalism and employee performance in a significant positive manner. Therefore, the company should continue to hold competitions for all levels/positions and divisions. It is possible to regularly schedule these Competency activities with similar agencies in order to broaden their horizons and experiences. This also applies to motivation.